Forms of psychopedagogical participation and intervention. (Journal of Parents and Teachers, 2014)
The school, the family and the children are all mutually enriched by the participation of families in the teaching and learning process. Within a global approach, the inclusion of families in schools in various fields, such as the educational or the advisor, can be worked on. Also, the article explains other aspects of parental involvement in schools.
Keywords: Teachers; families; family participation.